2009
DOI: 10.1080/10731190902743149
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Brain Injury or Peripheral Nerve Injury on Calcitonin Gene-Related Peptide Concentration Variation and Fractures Healing Process

Abstract: To investigate the changes of calcitonin gene-related peptide (CGRP) in rat's blood plasma, spinal anterior motorneuron, and dorsal root ganglion (DRG) after fractures combined with central or peripheral nerve injuries and its influence on fracture healing, 72 healthy adult SD rats (male or female) were divided into 4 groups (18 rats in each group): group A, simple(left) tibial fracture; group B, left tibial fracture combined with left sciatic nerve injury; group C, left tibial fracture combined with T9-11 spi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
26
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 10 publications
1
26
0
Order By: Relevance
“…This finding shed some light upon the process by which CGRP influences fracture recovery. Consistently, another research study had a similar result when a bone fracture combined with cerebral cortex injury demonstrated a faster healing process [14]. Although in our study we did not deeply investigate the relationship between brain injury and fracture healing, we discerned the high levels of NPY and CGRP during healing process in the injured areas, indicating a potential relationship between these two types of neurotransmitters and fracture healing.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…This finding shed some light upon the process by which CGRP influences fracture recovery. Consistently, another research study had a similar result when a bone fracture combined with cerebral cortex injury demonstrated a faster healing process [14]. Although in our study we did not deeply investigate the relationship between brain injury and fracture healing, we discerned the high levels of NPY and CGRP during healing process in the injured areas, indicating a potential relationship between these two types of neurotransmitters and fracture healing.…”
Section: Discussionsupporting
confidence: 72%
“…Li et al found that CGRP had a positive effect on mineralization and remodeling of bone by regulating NOS [13]. Zhang et al claimed that CGRP participated in bone metabolism and promoted swifter fracture healing [14]. Moreover, in a recent study, Tian et al confirmed that CGRP promoted osteogenic differentiation as well as proliferation [15].…”
Section: Introductionmentioning
confidence: 57%
“…The peripheral nervous system may play an important role in bone healing following fracture or other trauma [4–6]. Bone fractures accompanied by peripheral nerve injuries heal slower [7] and sensory denervation negatively affects long-term prognosis[8]. Substance P (SP), a neuropeptide belonging to the tachykinin family, is widely distributed in the body, particularly in the central and peripheral nervous systems where it acts as a neurotransmitter or neuromodulator [9].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies focused primarily on the damaged peripheral nerves themselves and denervated muscle [18,19]. Although bone healing combined with peripheral nerve injury has been investigated [4,5,7,8], interventions for denervated bones have not been extensively studied. This study measures the effects of combining treadmill running with Jiaji-EA on tibia bone mass, bone strength and SP expression in rabbits with sciatic nerve injury.…”
Section: Introductionmentioning
confidence: 99%
“…CGRP plays a well-recognized and pivotal role in repairing tissue, activating its cognate G protein-coupled receptor to initiate intracellular signaling2223. Following tissue injury, such as SCI, increased CGRP participates in vasodilation, sensory transmission, immune modulation and nerve regeneration2425262728. Recently, MSCs were found to express CGRP receptors on the cell membrane surface2930.…”
mentioning
confidence: 99%